2020
DOI: 10.1111/jdv.16241
|View full text |Cite
|
Sign up to set email alerts
|

Rosacea as a striking feature in family members with a STAT1 gain‐of‐function mutation

Abstract: Generation of full-thickness skin equivalents using hair follicle-derived primary human keratinocytes and fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…A higher prevalence among monozygous twins and association with two single nucleotide polymorphisms have been reported in the literature 5,6 . It has been reported that family members with a gain‐of‐function mutation in STAT1 show a phenotype of early‐onset rosacea 7 …”
Section: Pathogenesismentioning
confidence: 98%
“…A higher prevalence among monozygous twins and association with two single nucleotide polymorphisms have been reported in the literature 5,6 . It has been reported that family members with a gain‐of‐function mutation in STAT1 show a phenotype of early‐onset rosacea 7 …”
Section: Pathogenesismentioning
confidence: 98%
“…The delicate host/ Demodex equilibrium may be tipped in favor of mite proliferation by various factors, including immunosuppression [ 61 88 ], diabetes [ 89 92 ]), vasodilatory-related factors [ 8 , 10 , 25 , 27 , 31 , 57 , 93 97 ], and/or sebaceous hyperplasia [ 8 , 10 , 51 , 98 ]. Initially, overproliferation of the mite is not clinically visible, giving rise to what could be called subclinical demodicosis, which can be observed in many skin conditions (including apparently healthy skin and any facial dermatosis), but is commonly encountered in ETR [ 97 ] (Fig.…”
Section: Demodex and Demodicosismentioning
confidence: 99%
“…Genetic factors are well-known to influence the risk of rosacea, 83 and the STAT 1 gain-of-function mutation is associated with familial rosacea 84 and demodicosis. 20,22 In our study, most of the pairs of subjects had a genetic link suggesting that genetic background is more important than just close contact with a subject with high Dd.…”
Section: Familial Casesmentioning
confidence: 99%